2012
DOI: 10.1103/physreva.86.043617
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the momentum current of an off-resonant ratchet

Abstract: We experimentally investigate the phenomenon of a quantum ratchet created by exposing a BoseEinstein Condensate to short pulses of a potential which is periodic in both space and time. Such a ratchet is manifested by a directed current of particles, even though there is an absence of a net bias force. We confirm a recent theoretical prediction [M. Sadgrove and S. Wimberger, New J. Phys. 11, 083027 (2009)] that the current direction can be controlled by experimental parameters which leave the underlying symmetr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…Our results are an important step towards the goal to experimentally observe quantum isoperiodic structures in the context of ratchet effects with cold atoms [26,27]. Moreover, we strongly believe that quantum activations deserve further analysis, both theoretically and experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are an important step towards the goal to experimentally observe quantum isoperiodic structures in the context of ratchet effects with cold atoms [26,27]. Moreover, we strongly believe that quantum activations deserve further analysis, both theoretically and experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…where σ z is the Pauli matrix. We note that in our previous experiments with kicked rubidium 87 BECs [16,17,[22][23][24], the BECs were prepared in the 5 2 S 1/2 F = 1 level and the kicking light had a frequency corresponding to transitions between the 5 2 S 1/2 F = 2 and 5 2 P 3/2 F = 3 levels. This produced a standing wave with a detuning of ∆ ∼ 6.8 GHz.…”
Section: Quantum Walks At Quantum Resonancementioning
confidence: 93%
“…Recently, by using the same variable x, a scaling law for the ratchet current was developed theoretically [24] and verified experimentally [25]. It was found that the ratchet current could be described solely by the single parameter x and furthermore there existed an inversion of ratchet current at some values of x.…”
Section: Theorymentioning
confidence: 94%
“…QRs are normally observed in the kinetic energy of the AOQKR, which will show a quadratic growth with time at kicking periods that correspond to such resonances. Ratchets away from QR were also recently investigated theoretically [24] and experimentally [25]. These studies showed that the behavior of the ratchet current could be understood using a single variable that encapsulated most of the important parameters of the system such as the pulse period, the kick number, the kick strength, and the spatial position of the kicking standing wave relative to the initial state.…”
Section: Introductionmentioning
confidence: 99%